(untitled) (Eurasian Journal of Philology Science and Education, 2025)
This article examines the category of modality from the perspective of the linguocultural space of the Kazakh language. Modality is understood as a multifaceted phenomenon that expresses the speaker’s attitude toward the message, the action, and the addressee; it relies not only on grammatical forms (mood, affirmation/negation) but also on cultural codes and discourse types. In Kazakh, modal meanings naturally intertwine with folk ethical measures, with the ritual-traditional sphere, as well as with norms of speech etiquette. The aim of the study is to systematize the types of modal meanings that emerge in conjunction with these cultural dimensions and to describe their functioning with regard to genre, pragmatic, and social parameters. The data for the study were drawn from the works of Abai, M. Auezov’s epic The Path of Abai, a corpus of Kazakh blessings and prohibitive formulas, as well as samples of traditional oratorical discourse. The methodological framework includes semantic-pragmatic analysis, linguocultural interpretation, and the contextual-descriptive method. The analysis reveals that, withIn Kazakh speech culture, prescriptions and prohibitions are predominantly cast in polite, considerate forms; domains of desire and permission intersect with ethical virtue; and strategies for achieving agreement rely on meanings of conjecture and possibility. Modal markers are shown to be not merely grammatical indicators but also the linguistic mirror of national worldview and social relations. The findings of the study show that modality, with its semantic fields of necessity, obligation, prohibition, permission, possibility, conjecture, and desirability, intersects with such genre patterns as blessings, oaths, prohibitive formulas, advice, and oratorical speeches, as well as with value codes such as entrusted covenant, sense of shame, sin and merit, hospitality, and unity. These conclusions have methodological significance for language teaching and for official and public communication. Keywords: discourse, linguocultural space, category of modality, cultural dimension, cognitive content.